Respuesta :
Answer:
[tex]f(g(-1))= 3[/tex]
Step-by-step explanation:
[tex]f(g(-1))= 2(-1 -1)+7[/tex]
[tex]f(g(-1))= 2(-2)+7[/tex]
[tex]f(g(-1))= -4+7[/tex]
[tex]f(g(-1))= +3[/tex]
Answer:
3
Step-by-step explanation:
Given twee functions f and g. The question is to find f(g(-1)). If you interpret f(g(-1)) then you can look at it, as two different questions on one. So split it up into two separate questions and answer them seperately.
1. Find the result of substituting the number x= -1 in g.
g(x)=x-1 substitute x= -1
g(-1) = -1 -1 = -2
2. Find the result of substituting the number x= -2 in f.
f(x) = 2(x) + 7 substitute x= -2
f(-2) = 2*-2 +7 = -4 + 7 = 3
So now you have found the result of f(g(-1)), which in this case turns out to be 3.